Portal hypertensive gastric mucosa: an endoscopic study. Issue 10 (October 1986) - Papazian, A; Braillon, A; Dupas, J L; Sevenet, F; Capron, J P
Abstract : The endoscopic features of the gastric mucosa in patients with cirrhosis have not been systematically investigated. In these patients, we observed an endoscopic aspect, consisting of multiple small erythematous areas, outlined by a subtle yellowish network (resembling a mosaic), mainly located in the proximal part of the stomach. We tested the value of this sign by comparing two groups: 100 patients with portal hypertension due to cirrhosis, and 300 control patients without signs of liver disease or portal hypertension. This endoscopic pattern was observed in 94 of the patients with cirrhosis, whereas oesophageal varices were seen in 78 only. In contrast, only one patient of the control group had this aspect. Moreover, this sign was also found in seven of eight patients with non cirrhotic portal hypertension, but was seen neither in 100 patients with chronic alcoholism but without liver disease, nor in 10 cirrhotic patients with end-to-side portacaval shunts. These endoscopic changes might be because of mucosal and/or submucosal oedema and congestion highlighting the normal areae gastricae pattern and related to raised portal pressure. We conclude that the mosaic pattern of the gastric mucosa is a sensible and specific sign for diagnosis of portal hypertension, whatever the cause.